AN ANALYSIS OF ILLOCUTIONARY ACTS AND FELICITY CONDITIONS IN THE DOCUSERIES TAYLOR SWIFT: THE END OF AN ERA - Reenad; Anisa Alawiyyah; Anisa Septia Megawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the categories of illocutionary acts and how their corresponding felicity conditions are fulfilled as observed in the docuseries Taylor Swift: The End of an Era. Unlike traditional linguistic studies, this qualitative research deliberately confines its scope strictly to the production of illocutionary forces and the essential criteria that render these communicative acts valid and successful, without including politeness or perlocutionary effects. To systematically analyze the language phenomena, this study employed a descriptive qualitative method as the research methodology. Data were collected from the utterances spoken by the main subject across six episodes through comprehensive transcribing, note-taking, and categorizing based on John R. Searle's theoretical framework. The findings revealed a total of 522 analyzed utterances spread across the categories. Among these classifications, assertive acts emerged as the absolute dominant illocutionary acts with 330 utterances, driven by the biographical nature of the docuseries to state facts, explain creative processes, and report past memories. Furthermore, the analysis of felicity conditions demonstrated that the sincerity condition was the most dominant criterion fulfilled with 358 utterances, establishing the linguistic validity, social contract, and psychological authenticity of the spoken utterances. In conclusion, this research highlights how pragmatic competence operates within public narratives. The results imply that understanding illocutionary structures enables a deeper comprehension of how public figures construct meaning, project authentic personas, and maintain communicative efficacy in contemporary media.